Isolation of Viable Single Cells With High Yield and Purity Using a Small Amount of Human Kidney Tissue Biopsy - Yaigoub, Hasnaa; Tirichen, Hasna; Xin, Xiaohong; Shi, Shuhong; Wu, Changxin; Li, Rongshan; Li, Yafeng (Frontiers in Cell and Developmental Biology, 2022)
Graphical Abstract